Experiential Intensity of Exploring Place Abandoned - Kevin Redmond (University of Alberta, 2021)
There is a growing global shift towards urbanization resulting in diminishing connections with the traditional rural placescape. Newfoundland and Labrador (NL) has a long history of out-migration and internal migration between communities in coastal areas within the province. Resettlement programs initiated by the NL government between 1954 and 1975 accounted for the internal migration of approximately 30,000 people from 300 communities. Modern-day encounters with these abandoned communities are relevant to understanding the loss of place and home, as significant numbers of students in NL today are affected by migration. This paper is a phenomenological study of the experiences of educators as they explored the remnants of an abandoned community. The participants of the study were six experienced public school educators with teaching experience at the primary, elementary, intermediate, and secondary levels. The study took place in eight abandoned communities located on the western shore of Placentia Bay, where mainly the remnants of Isle Valen, St. Leonard’s, St. Kyran’s, and Great Paradise were explored. Data collection consisted of two personal interviews and one group hermeneutic circle, with the aim to answer one fundamental question: What is the experience of educators exploring the remnants of an abandoned community? Data in this study are represented by lived experience descriptions, which were interpreted hermeneutically and guided by four phenomenological existentials: temporality, corporeality, spatiality, and relationality. The results of this study not only provide deeper insight into intense experiences in communities abandoned through resettlement; they also reveal the significance of place in our lives, place as heuristic teacher, the pedagogical power of place, the need for local, meaningful place-based experiences in a curriculum as lived, and their potential for furthering personal and educational insight no matter where in this world we live or dwell.